2011
DOI: 10.3109/0886022x.2010.541578
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Sleep Quality and Heart Rate Variability in Hemodialysis Patients

Abstract: Introduction: Sleep disturbances and cardiovascular autonomic dysfunction are major complications of hemodialysis (HD). The goal of this study is to identify clinical, heart rate variability (HRV) or laboratory parameters that are independently associated with subjective sleep quality. Patient and methods: Forty-six stable HD patients filled out sleep questionnaires -Pittsburgh sleep quality index (PSQI), Athens insomnia scale (AIS), and Epworth sleepiness scale (ESS). In addition, they received analyses of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…It seemed to be caused by impairment of the cardiovascular autonomic control characterized by withdrawal in parasympathetic modulation and predominance in sympathetic tone (28). As in previous studies (17)(18)(19)(20)(29)(30)(31)(32)(33), our results showed that stage 5 CKD patients exhibited a marked reduction in HRV indices relative to age-and sex-matched controls, indicating that sympathetic hyperactivity may play an important role in increasing the risk of CVD among ESRD patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It seemed to be caused by impairment of the cardiovascular autonomic control characterized by withdrawal in parasympathetic modulation and predominance in sympathetic tone (28). As in previous studies (17)(18)(19)(20)(29)(30)(31)(32)(33), our results showed that stage 5 CKD patients exhibited a marked reduction in HRV indices relative to age-and sex-matched controls, indicating that sympathetic hyperactivity may play an important role in increasing the risk of CVD among ESRD patients.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have shown a marked reduction of HRV indices in ESRD patients (17)(18)(19)(20). To our knowledge, few studies have evaluated the correlation between SHPT and HRV in ESRD patients.…”
Section: Introductionmentioning
confidence: 98%
“…We found no relationship between the ESS value and HR or HRV measurements; previous studies in other populations also found little relation. 54 , 55 Sleep quality scores, referring to the night of PSG specifically, showed only very small correlations, being inversely related to the mean HR in wake ( R =−0.13) and the percentage HR dipping ( R =−0.12). The former relation is plausible, if perhaps higher HR during wake reflects a form of hyperarousal that influences the perception of sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The auricular branch of the vagus nerve links the acupressure stimulation and vagal regulation. AAT might trigger vagal regulation and correct the overactivity of sympathetic nerves which plays a crucial role in chronic hemodialysis patients with insomnia [ 20 ]. Therefore, auricular acupressure might be effective in improving sleep quality for hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%